Splenomegaly, elevated alkaline phosphatase and mutations in the SRSF2/ASXL1/RUNX1 gene panel are strong adverse prognostic markers in patients with systemic mastocytosis - Jawhar, Mohamad; Schwaab, Juliana; Hausmann, Daniel; Clemens, Maja Josefine; Naumann, Nicole; Henzler, Thomas; Schönberg, Stefan; Fabarius, Alice; Hofmann, Wolf-Karsten; Metzgeroth, Georgia; Reiter, Andreas (Leukemia, 2016)
We evaluated the impact of clinical and molecular characteristics on overall survival (OS) in 108 patients with indolent (n=41) and advanced systemic mastocytosis (SM) (advSM, n=67). Organomegaly was measured by magnetic resonance imaging-based volumetry of the liver and spleen. In multivariate analysis of all patients, an increased spleen volume 450 ml (hazard ratio (HR), 5.2; 95% confidence interval (CI), (2.1-13.0); P=0.003) and an elevated alkaline phosphatase (AP; HR 5.0 (1.1-22.2); P=0.02) were associated with adverse OS. The 3-year OS was 100, 77, and 39%, respectively (P<0.0001), for patients with 0 (low risk, n=37), 1 (intermediate risk, n=32) or 2 (high risk, n=39) parameters. For advSM patients with fully available clinical and molecular data (n=60), univariate analysis identified splenomegaly 1200 ml, elevated AP and mutations in the SRSF2/ASXL1/RUNX1 (S/A/R) gene panel as significant prognostic markers. In multivariate analysis, mutations in S/A/R (HR 3.2 (1.1-9.6); P=0.01) and elevated AP (HR 2.6 (1.0-7.1); P=0.03) remained predictive adverse prognostic markers for OS. The 3-year OS was 76 and 38%, respectively (P=0.0003), for patients with 0-1 (intermediate risk, n=28) or 2 (high risk, n=32) parameters. We conclude that splenomegaly, elevated AP and mutations in the S/A/R gene panel are independent of the World Health Organization classification and provide the most relevant prognostic information in SM patients.